Analysis of Growth data of Physical Characteristics of Indian Tiger (Panthera tigris tigris) at Panna Tiger Reserve - Kumar Sharma, Uttam; Jarande, Ishwar; Kumar Gupta, Sanjeev (Indian Forester, 2022)
The importance of the presence of the Indian tiger (Panthera tigris tigris) in the Indian forest as an apex predator cannot be understated. The Government of India along with State Governments is running various programs for protecting tigers in the wilderness. This includes the reintroduction of tigers in those forested areas where currently tiger has no presence due to local extinction or in areas where tiger numbers are very low and the threat of their becoming locally extinct looms large. Reintroduction by translocating seven tigers to PTR, six from the other three tiger reserves of MP and one from Bhopal forest division, between the year 2009 and 2014, under 'Species Recovery and Reintroduction Project' has led to establishing a healthy tiger population in PTR within 10 years. The whole process of reintroduction has not only generated immense management experience but in this process, sufficient data has been gathered of tiger physical characteristics like weight, total length, neck, chest and abdomen girth, shoulder height, and canine size at different ages. As data regarding the body growth of a tiger in wild is mostly unavailable, this paper presents analysis of collected data and growth curves for these body parameters of wild tigers, both male and female. It will be very useful not only for those who are looking for physical characteristics in absolute terms and body growth rate of tigers in wild for academic purposes but also for those managers who are looking for tiger reintroduction in their area for taking appropriate decisions. Further as the genetic diversity of PTR tigers structurally represent genetic mixture of tigers of whole of Central India, the data collected of tigers of PTR may be used for all Central Indian tiger populations. Also, we can build on this to have an All India Booklet on Tiger Body Growth Data representing all regions of the country.